Competing invaders: Performance of two Anguillicola species in Lake Bracciano. Issue 1 (April 2015) - Dangel, K.C.; Keppel, M.; Le, T.T.Y.; Grabner, D.; Sures, B.
Highlights: Two Anguillicola spp. occurring as nonindigenous species are compared in the review. Both species differ in their life cycles. Anguillicola crassus replaced Anguillicola novaezelandiae in Lake Bracciano. Possible reasons for the disappearance of A. novaezelandiae are discussed. Graphical Abstract: Abstract: Anguillicola crassus is one of the most successful parasitic invasive species as it has spread from its original habitat in East Asia throughout the world and has acquired five new eel host species in the course of its invasion within the last three decades. Records from an Italian lake indicate that this species has even displaced an established population of its close relative A. novaezelandiae originating from New Zealand. In order to analyze the reasons for its high invasive potential, this review highlights recent studies, which substantiate the selective advantages of A. crassus over A. novaezelandiae. Laboratory infection experiments revealed that A. crassus features a less synchronized development compared to A. novaezelandiae in the European eel, which enables this species to emit eggs over a longer period of time. Differences in the time period required for first egg output and in the maturation process of second stage larvae in intermediate hosts could also be detected, which may lead to differences in infection potential. Finally, microsatellite analyses have shown that hybridization processes are possible, but might only occur between A. crassus males and A. novaezelandiae females. Taken as a whole, the sum of minor selective advantages and differences in life cycle traits could have considerably contributed to a replacement of one species by the other.